Critical issues in soft rocks - Milton Assis Kanji (Journal of Rock Mechanics and Geotechnical Engineering, 2014)
This paper discusses several efforts made to study and investigate soft rocks, as well as their physico-mechanical characteristics recognized up to now, the problems in their sampling and testing, and the possibility of its reproduction through artificially made soft rocks. The problems in utilizing current and widespread classification systems to some types of weak rocks are also discussed, as well as other problems related to them. Some examples of engineering works in soft rock or in soft ground are added, with emphasis on their types of problems and solutions.